Farmer organizations in ubon ratchathani province - Prathanthip Kramol (2020)
© The Author(s) 2020. Notwithstanding the rapid growth of commercial agriculture in Thailand over the past half century, farmer organizations and community enterprises have been a common and distinctive feature of the rural economy and have been strongly supported by government policies, especially with the promotion of the “sufficiency economy”. While informal cooperation has been a traditional part of village life, the government has consistently promoted more formal organizational arrangements for farmers, alongside policies for intensification and commercialization of rice and other crops. This juxtaposition of independent smallholder farming and collective, community-based economic activity is explored in this chapter through case studies of organizations in three villages in Northeast Thailand. It was found that farmer organizations can facilitate the sharing of knowledge and skills, improve access to production technologies, encourage saving and investment, and increase farmers’ market competitiveness. Community enterprises can create new employment opportunities, especially for women and disadvantaged groups, contributing to livelihood diversification while reducing the need for out-migration. The key factors contributing to the success of these groups were strong committed leadership, involved membership, connecting with wider networks, the role of government and non-government assistance providers, and supportive government policies.